Computational analysis and detection of Bengali communal violent speech - Khondoker, Abdullah; Taufik, Enam Ahmed; Tashik, Md. Iftekhar Islam; Mahmud, S M Ishtiak (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.